Presencia del síndrome de Burnout en el profesional de Enfermería en las áreas críticas del Hospital Teófilo Dávila de Machala. - Rodríguez Naranjo, Alejandra Stefhany (2018)
Burnout syndrome is a state of exhaustion, physical, emotional and mental, accompanied by a decrease in performance capacity, preceded by a phase of loss of motivation for their work, feeling emotionally exhausted, disappointed and frustrated, forming one of the main causes of deterioration of working conditions. The research "PRESENCE OF THE BURNOUT SYNDROME IN THE NURSING PROFESSIONAL IN THE CRITICAL AREAS OF HOSPITAL TEÓFILO DÁVILA DE MACHALA" has the main objective of determining the presence of the Burnout Syndrome in the nursing professional in the critical areas of the Hospital Teófilo Dávila de Machala To do so, a descriptive, cross-sectional and quantitative study methodology was proposed. A self-made survey was used as measurement instruments, in which socio-demographic, labor and occupational health aspects are valued, as well as the Maslach Burnout Inventory (MBI), a validated instrument for the measurement of the syndrome. The universe was made up of 79 nursing professionals obtaining the following results: The presence of Burnout Syndrome was obtained that do not present this syndrome and are at a medium level with 65.8%, however they tend to increase becoming a risk factor in his performance and dealing with patients. The results will help to implement actions, aimed at preventing the development of the syndrome in this group, preserving the health of nursing professionals. Keywords: Burnout syndrome, Critical areas, MBI Nursing.